Future Interaction between Man and Robots from Islamic Perspective - Dahlan, Hadi Akbar (International journal of islamic thought, 2018)
Technology improves exponentially every second and becomes more complex beyond our grasp. Without we realize, everything about ourselves can be found on the internet from mundane things such as our food preferences to private matters such as saving accounts. To manage these information, an artificial intelligence system is required to safeguard, validate and even facilitate our daily tasks. Hypothetically, this issues will lead to the creation of Artificial General Intelligence (AGI), a (hypothetical) machine that could successfully perform any intellectual task that a human being can. Without a doubt, AGI will be a central component to our future society. As AGI further improved itself, roaming fully robotic android may be a common sight in future cities. This is a common plot setting in science fiction stories and is commonly discussed from Western perspective. However, this issue is rarely discussed from the Islamic perspective. Will AGI differentiate between fitna and facts (tabayyun)? Is a humanized android considered human (nas)? Does matter of fiqh relevant to a humanized android? Although seems fictional, it is imperative for the Muslim world to initiate discussion on these issues.